Greenhouse gases as clues to permanence of farmlands - Janzen, H Henry (Conservation biology : the journal of the Society for Conservation Biology, 2007)
Farmlands are expansive, diverse, and intensively managed ecosystems. These lands, so critical to human welfare, are threatened by growing stresses as demand for food escalates, fresh water wanes, cheap fuels deplete, and other uses jostle for space. With these coming pressures, how can we foster permanence on the lands that sustain us? In this essay I contemplate the hypothesis that the greenhouse gases, because they emanate from the interwoven flows of C, N, and energy in ecosystems, can help steer us toward permanence (sustainability). Alongside other indicators these emissions may detect the ecosystem's pulse, alerting us to inefficiencies and guiding us to better practices. To be effective signals, however, the greenhouse gases will need to be considered in their local settings, monitored longer and in more "listening places," and measured across boundaries of disciplines and biomes. This approach may help reduce greenhouse gas emissions from our farmlands. But we may find that, in the long run, the main beneficiaries of our inquiry have been, not just the atmosphere, but our fragile lands, perhaps in ways we cannot yet foresee